Pendidikan Dan Perubahan Sosial SMP Al–Munawwir Sangatta Selatan - Jusmala Jusmala; Meta Fauziah; Muhammad Yasin (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the role of education as an agent of social change at Al-Munawwir Junior High School in South Sangatta, focusing on the synergy between the school, teachers, and parents. A qualitative case study method was used through in-depth interviews, observations, and documentation studies. The results indicate that the integration of values ​​such as discipline and environmental awareness into the hidden curriculum serves as a vehicle for social change. Positive teacher-student interactions serve as role models and strengthen the legitimacy of the values ​​of change. The principal's transformational leadership and teacher commitment are dominant factors in success, while the digital literacy gap between students and parents is a major obstacle. The study confirms that the sustainability of social change at this school depends on the synergy of the school ecosystem and structured community support.